Contributions of livestock holdings to the environment objectives improvement - Rodica Chetroiu; Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The complexity of the relations between agriculture and environment has created the need to introduce environmental issues into the CAP. The principle of good agricultural practices is essential to understand this relation between agriculture and environment. Environmental measures in agriculture aim at the animal farm activity takes place in accordance with the recommended technologies and livestock waste management in conditions of minimum impact on the environment factors. In this paper, it estimates the annual production of organic fertilizer from farm activity, the quantities of nutrients (nitrogen, phosphorus and potassium) resulting from these, and the areas of agricultural land that can be fertilized with these quantities. The calculations took into account farm modules for the following products: cow's milk, sheep's milk, goat's milk, beef, pork, poultry, and eggs for consumption.
Keywords: 330; environment; animal husbandry; fertilizers; organic; agricultural holding